(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper explores the relationship between decentralization and political stability in India, focusing on the implementation of political, administrative, and fiscal decentralization. It analyzes the successes and challenges faced by local governance structures and highlights opportunities for strengthening decentralization to promote political stability. Through case studies from Indian states like Kerala and Karnataka, the paper provides policy recommendations aimed at enhancing the autonomy, capacity, and inclusiveness of local governments.